HUBUNGAN DUKUNGAN SOSIAL KELUARGA TERHADAP KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIS YANG MENJALANI HEMODIALISA DI RSU PKU MUHAMMADIYAH GOMBONG - Sugeng Riyadi, Taufiq; -, Handoyo; Tamara Yuda, Hendri (Jurnal Ilmiah Kesehatan Keperawatan, 2014)
Individual with long-term hemodialysis often feel worried about the pain and disruption in his life. They usually face financial problems, difficulty in retaining his job, sex drive is gone even impotence, depression due to chronic pain and the fear of death. Planned lifestyle associated with dialysis therapy, and restriction of fluid intake and often eliminate the spirit of life of patients and their families. This will affect the quality of life of patient The aim of this study is to show the relationship between family social support with the quality of life in patients with chronic renal failure undergoing hemodialysis in PKU Muhammadiyah Gombong Hospital. This study used analytic correlation with cross sectional approach. The number of respondent is 44 patient suffering chronic renal failure. Total sampling method was used to chose respondent. Data where collected by social support family and quality of life quitionare. Data collected were analyzed by computer program. The results of this study indicate the data obtained from 44 respondents there were 21 respondent  (47.7%) who received social support both families have good-quality life while respondents who received social support was having a good quality of life for as many as 8 respondent ( 18.2%). From the results of the chi square test statistic was found that the value of X ² calculated> X ² table is 5057> 3.8414. And views of the value of p on the fisher’s exact test sebesar 0.037 which means p <0.05 means that there is a relationship between social support for families with quality of life in patients with chronic renal failure undergoing hemodialysis in PKU Muhammadiyah Gombong Hospital.   Keywords: family sosial support, quality of life, chronic renal failure, hemodialysis